Website as an e-Commerce Tool: Regulatory Technology - RYZHIK, Andrey Vladimirovich; SLESAREV, Vladimir Lvovich; MALCEV, Vitalij Anatolevich; KAMISHANSKY, Vladimir Pavlovich (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).37, 2020)
This paper presents an analysis of the legal nature and regulation features of the website, which is the main tool of electronic commerce. There are various definitions of the concept of website that reflect the legal nature of the definition in question, depending on the circumstances of its use. It has been established that a website refers to a set of electronic documents (files), united under one address (domain name and (or) IP address). The authors come to the conclusion that, depending on the business model used by the subject of electronic commerce, websites can have both an informational and advertising character and contain the functionality of online stores, accepting and processing orders for goods and services online and, in many cases, performing them as well. With a certain degree of conventionality, one can say that in modern conditions the website acts as a representative of the person on the Internet. Therefore, the very first stage of its use — the stage of creating a website — is particularly important.